Biological Fixation of AC Joint using Autologous Semitendinosus Graft in Acute Type III-VI Acromioclavicular Joint Dislocations—A Pilot Study - Ashish K. Shukla; V. P. Thulasidharan; Ashish Pande; Anil K. Mishra; Aditya Dwivedi (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Introduction: Injuries to the acromioclavicular (AC) joint can range from modest, transient pain to significant displacement, chronic pain, and shoulder biomechanical changes that result in long-term disability. Aim and Objective: We aimed to evaluate the functional outcome of anatomical reconstruction of ACJ using autologous semitendinosus graft in type III-VI AC joint dislocations. MATERIALS AND METHODS: In this study, 20 patients with AC joint dislocation (Rockwood type III-VI) were managed by surgical fixation using autologous semitendinosus graft from November 01, 2019, to October 31, 2020, at our center. After providing written informed consent, the study enrolled patients who satisfied the inclusion criteria. Preoperative, three-month, and six-month UCLA shoulder scores were assessed. Results: Mean age of participants was 36.5 years (SD: 9.86). Radiological evaluation at each visit suggested a 100.0% success rate of this method. 95% of the participants had no complications, while 5.0% had DVT. No participants had SSI. Conclusions: Autologous semitendinosus graft fixation of type III-VI AC joint injuries is a viable surgical option with the advantages of being a biological fixation, single surgery, and having excellent functional outcomes. However, extensive multicentric comparative studies are required to draw definitive conclusions.